2024
DOI: 10.1186/s12916-024-03257-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization and immunotherapy for microsatellite instability-high in cholangiocarcinoma

Xu Yang,
Baofeng Lian,
Nan Zhang
et al.

Abstract: Background Microsatellite instability-high (MSI-H) is a unique genomic status in many cancers. However, its role in the genomic features and immunotherapy in cholangiocarcinoma (CCA) is unclear. This study aimed to systematically investigate the genomic characterization and immunotherapy efficacy of MSI-H patients with CCA. Methods We enrolled 887 patients with CCA in this study. Tumor samples were collected for next-generation sequencing. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Similarly, high TMB is a widely used immunotherapy predictive biomarker, but the majority of BTC patients show low TMB, with a median value of approximately 3.7 Muts/Mb. 34 In the present trial, there was only one patient with high TMB/MSI‐H status who obtained PR and is still receiving maintenance sintilimab treatment. Recently, several studies have indicated that PD‐L1‐positive expression is associated with improved therapeutic outcomes, but the specific cutoff values of PD‐L1‐positive tumor cells (tumor cell proportion score, TPS) or tumor cells plus tumor‐associated immune cells (combined positive score, CPS) are not clear.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, high TMB is a widely used immunotherapy predictive biomarker, but the majority of BTC patients show low TMB, with a median value of approximately 3.7 Muts/Mb. 34 In the present trial, there was only one patient with high TMB/MSI‐H status who obtained PR and is still receiving maintenance sintilimab treatment. Recently, several studies have indicated that PD‐L1‐positive expression is associated with improved therapeutic outcomes, but the specific cutoff values of PD‐L1‐positive tumor cells (tumor cell proportion score, TPS) or tumor cells plus tumor‐associated immune cells (combined positive score, CPS) are not clear.…”
Section: Discussionmentioning
confidence: 70%